(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Guadalquiver DME, Nuneza OM, Villanueva RJT. 2022. Odonatofauna in the freshwater system of Kibalabag, Malaybalay City, Bukidnon, Philippines. Biodiversitas 23: 1857-1863. Despite the critical importance of freshwater ecosystems to human populations and biodiversity, many anthropogenic practices continue to imperil such habitats. An excellent way to monitor the integrity of these ecosystems is through bioindicator organisms like insects of order Odonata, which are highly sensitive to environmental changes. In Malaybalay City, Philippines, the freshwater system in barangay Kibalabag is the primary source of potable water. Thus, to gain insight into its integrity and health, the present study seeks to determine adult Odonata species composition and diversity in the area. Opportunistic sampling using sweep netting and handpicking was conducted in four sampling sites. Twenty-five species were identified, comprising 230 individuals under nine families and 21 genera. Endemism of 65% (17 species) was recorded, with five species exclusive to Mindanao Island and three species classified as threatened. A high ratio of Zygopterans to Anisopterans, indicative of pristine conditions, was observed. Computation of biodiversity indices revealed that Site 2 (Wetland) is the most diverse (H’: 2.582) due to habitat variability. Cluster analysis also showed that Sites 1 (Kibalabag falls) and 2 were most similar. Species assemblage in these sites and high richness in Site 1 demonstrated high habitat integrity and good water quality, whereas the species assemblage in Sites 3 and 4 connotes habitat disturbance. The high endemicity and moderate diversity showed that the area is a healthy and suitable habitat for Odonata, emphasizing the need for its conservation and proper management.